Labour productivity and firm entry and exit in manufacturing - Anni Nevalainen (The Research Institute of the Finnish Economy (ETLA), 2008)
This paper investigates the connection between firm entry and exit and labour productivity growth. The study has its theoretical foundations in modern Schumpeterian growth theory, distance to frontier model and vintage capital models. The importance of productivity enhancing restructuring has been increasingly acknowledged and all these theories depict the productivity enhancing effects that external restructuring - in particular firm entry and exit - may have. Despite the vast theoretical discussion there is only a little empirical research on the subject. Thus, this study aims at contributing to the existing empirical literature by utilizing panel data that contain information on all manufacturing subsectors from eight EU member states between 1997 and 2004. Empirical analysis is conducted with fixed effects panel regression. It is noted that firm turnover, especially firm entry enhances productivity growth, but the effects appear with a lag. Productivity enhancing effects of firm entry are the strongest three years after the initial entry. The effects of firm exit on labour productivity growth are also positive but more modest than the effects of firm entry. Results of the analysis suggest that the population of firm entrants is extremely heterogeneous.
Keywords: L6; O4; 330; Labour productivity; manufacturing; firm entry; firm exit; modern Schumpeterian growth theory; Verarbeitendes Gewerbe; Arbeitsproduktivität; Markteintritt; Marktaustritt; Schumpeterismus; EU-Staaten